Revolutionizing Global Administration: PATEN Excellence Unveiled - Mursyidah, Lailul; Rafsanjani, Moch. Jalaluddin (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates the quality of Integrated Administrative Services (PATEN) in the Dlanggu sub-district office, Mojokerto Regency. Utilizing a descriptive research design with a qualitative approach, the performance of administrative service employees is analyzed. Data collected through interviews, observation, and documentation reveal that service speed is commendable, and employee politeness and friendliness are satisfactory. While some service quality indicators are met, the overall service quality in Dlanggu District is deemed good and reasonably optimal. The study identifies both supporting factors and constraints affecting employee performance. This research contributes to the understanding of integrated administrative services and suggests potential areas for improvement in Dlanggu District, providing insights applicable to similar contexts globally. Highlight : Performance Assessment: Utilizing a qualitative approach, this study evaluates the performance of employees providing Integrated Administrative Services (PATEN) in Dlanggu Sub-District, offering insights into service quality indicators and efficiency. Supporting Factors and Constraints: Through interviews and observation, the research identifies key factors influencing employee performance, shedding light on both supporting elements and constraints that impact the delivery of integrated administrative services. Global Applicability: The study's findings contribute to the broader understanding of administrative service quality, providing valuable insights applicable to diverse contexts beyond Mojokerto Regency, with implications for global practitioners and policymakers. Keywords: Integrated Administrative Services, Performance Analysis, Dlanggu Sub-District, Service Quality, Mojokerto Regency